Characteristics of Tension-Type Headache among Nurse in Udayana University Hospital - Savitri, Ni Putu Sista Ijya; Wijayanti, Ida Ayu Sri; Widyastuti, Ketut; Indrayani, Ida Ayu Sri (E-Jurnal Medika Udayana; Vol 12 No 8 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i08.P12, 2023)
Background: Headache is the most common complaint experienced by people in the world with the highest prevalence spesifically tension-type headache. Nurses are one of the professions with the risk of experiencing tension-type headache that can affect performance, costs, and work results. The purpose of this study was to determine the prevalence and characteristics of tension-type headache among nurses who work in the hospital. Method: This research is a cross-sectional descriptive study with consequtive sampling technique involving 89 nurses at Udayana University Hospital using primary data obtained from questionnaires (google form) and then analyzed by using SPSS 26. Results: The results showed that the prevalence of tension-type headache in nurses was 46.1%. Based on the most common characteristic in nurses, spesifically within the age of 26-35 years about 80.5%, female gender about 65.9%, obesity category about 39%, no stress category about 95.1%, sleep duration > 6 hours about 58.5%, shift nurses about 92.7%, nurses in inpatient room about 70,7%, and below 3 years duration of work about 80.5%. Conclusion: The prevalence of tension-type headache in nurses is 46.1% with the most characteristics at the age of 26-35 years (early adulthood), female gender, dominated by obesity category, no stress category, sleep duration > 6 hours, dominant in shift nurses, mostly in inpatient room nurses and below 3 years duration of work. Keywords: Tension-type headache, characteristics, nurse